A pilot study on validation of the International Society for the Prevention of Child Abuse and Neglect Child Abuse Screening Tool-Children's Version (ICAST-CH) - Sahaimi, Mohd Faizul (2016)
Background Childhood maltreatments, which include all forms of abuse namely physical, sexual, emotional or psychological abuse and neglect undeniably is a very crucial problem across the continents, cultural and beliefs. Despite the alarming increasing in rates and prevalence of such maltreatments all over the world, the true extent of the problem remains a conundrum. There are multitudes of studies carried out in an attempt to explore this pressing problem, but the mysteries have yet to be solved. The International Society for the Prevention of Child Abuse and Neglect (ISPCAN), has developed an instrument ICAST-CH specifically designed for children. This instrument proved to be reliable in accessing the scope and prevalence of childhood maltreatment. Malaysia, in particular, has very limited tools to assess childhood experiences of maltreatment. Objective The study aimed at translating and validating Malay version of ISPCAN Child Abuse Screening Tool – Children's Version (ICAST- CH) among Malaysian children. Methods A two-phase study was conducted. In phase I, the ICAST-CH English Version was translated into Malay using forward and backward translation procedure and following that, the content validity was obtained. In phase II, 253 students, aged 13 to 17 years old were recruited by universal sampling method to examine internal consistency by mean of Cronbach's alpha and to explore construct validity by mean of exploratory factor analysis. Results Analysis of the study indicated that Malay version ICAST-CH-M had high total score internal consistency with Cronbach's alpha of 0.84, but low on subscale that ranged from 0.61-0.81. Conclusion This study failed to demonstrate satisfactory reliability and validity for ICAST-CHM. Thus the recommendation to use ICAST-CH-M as an instrument to measure childhood maltreatment's among Malaysian children could not yet be concluded. Further study to explore the instrument is highly recommended.